2021
DOI: 10.1111/evo.14300
|View full text |Cite
|
Sign up to set email alerts
|

Clinal and seasonal changes are correlated in Drosophila melanogaster natural populations

Abstract: Spatial and seasonal variations in the environment are ubiquitous. Environmental heterogeneity can affect natural populations and lead to covariation between environment and allele frequencies. Drosophila melanogaster is known to harbor polymorphisms that change both with latitude and seasons. Identifying the role of selection in driving these changes is not trivial, because nonadaptive processes can cause similar patterns. Given the environment changes in similar ways across seasons and along the latitudinal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 103 publications
(195 reference statements)
1
11
1
Order By: Relevance
“…In the same manner, temperate populations from North America and Europe demonstrate parallel seasonal allele frequency change across the two continents 13 . Together, these results support that seasonal adaptation could be a general phenomenon of temperate Drosophila populations 12 14 .…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…In the same manner, temperate populations from North America and Europe demonstrate parallel seasonal allele frequency change across the two continents 13 . Together, these results support that seasonal adaptation could be a general phenomenon of temperate Drosophila populations 12 14 .…”
Section: Introductionsupporting
confidence: 76%
“…Seasonal fluctuations are main sources for rapidly changing environments in temperate regions and recent studies provided evidence for rapid change in SNP frequencies among seasons 12 14 . Previous studies also revealed that seasonal variation in adaptive phenotypic traits like thermal and starvation tolerance 22 , and innate immunity 25 in D. melanogaster populations and all together suggesting that many loci respond to seasonal selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations